PARTY POSITIONS ON THE EUROPEAN UNION IN THE BALTIC STATES: DO THEY COMPETE? DO THEY MIRROR VOTERS’ POSITIONS? - Bekišas, Tomas (Baltic Journal of Political Science, 2018)
This paper aims to determine Lithuania’s, Latvia’s, and Estonia’s parties’ positions on the European Union (EU) and to ascertain whether these party positions mirror their voters’ positions on the EU. Analysis suggests that parties in this region have rather varied positions on the EU, with the exception of hard-Eurosceptic views, which are absent in Baltic states’ party systems. This paper also indicates that parties in the Baltic states tend to mirror, with some exceptions, their voters positions on the EU. This suggests that there may be additional factors determining parties’ positions regarding the EU in the Baltics.